2017
DOI: 10.1111/jfbc.12390
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical composition and antioxidant activity of Tunisian cactus pear (Opuntia ficus indica L.) flower

Abstract: The aim of this work was to characterize Tunisian cactus pear (Opuntia ficus indica L.) flower through its lipids, essential oils, phenolics, and antioxidant activity. The total lipid content of cactus pear flower was about 2% with the neutral lipid amount, especially monoacylglycerols, being the highest. The lipids were rich in linoleic, oleic, and palmitic acids. The essential oil yield was 0.01% with the presence of 29 components in a complex mixture of monoterpenes. The main components of the essential oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Opuntia ficus‐indica L. Miller (cactus pear, prickly pear or nopal cactus) belongs to the Cactaceae family and is native to Mexico. This plant can be found either in coastal regions or plateaus of the arid and semi‐arid regions of South and Central America, Africa and the Mediterranean region (El‐Mostafa et al, ; Mottese et al, ; Ouerghemmi et al, ). At this moment, O. ficus‐indica is cultivated in more than 30 countries of both hemispheres.…”
Section: Introductionmentioning
confidence: 99%
“…Opuntia ficus‐indica L. Miller (cactus pear, prickly pear or nopal cactus) belongs to the Cactaceae family and is native to Mexico. This plant can be found either in coastal regions or plateaus of the arid and semi‐arid regions of South and Central America, Africa and the Mediterranean region (El‐Mostafa et al, ; Mottese et al, ; Ouerghemmi et al, ). At this moment, O. ficus‐indica is cultivated in more than 30 countries of both hemispheres.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products’ ability to reduce metals is regarded as a key marker of their antioxidant properties [ 76 ]. Spectroscopically, the quantity of ferric (Fe 3+ ) complex conversion to ferrous (Fe 2+ ) form is detected by the color change of the solution based on the compound’s ability for reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the flowers, a study by Chahdoura et al [ 59 ] on the flowering stage of O. microdasys demonstrated that ferulic acid and isorhamnetin derivates were the most frequent, ranging from 1.24–2.95 mg/g and 4.68–23.04 mg/g, respectively, while Ammar et al [ 65 ] found a higher content in quinic acid and quercetin derivates, with 1.32 and 8.50 mg/g, respectively, for O. ficus-indica flowers. Moreover, Ouerghemmi et al [ 54 ] reported that ferulic acid and quercetin were in higher amounts when compared to other phenolic compounds in O. ficus-indica flowers. It seems evident, based on the available studies, that besides the abiotic factors, the species-specific ones have a significant role in phenolics’ concentration and distribution throughout the different plant tissues.…”
Section: Phenolic Compoundsmentioning
confidence: 99%